Improved frequency selective fat suppression in the posterior neck with tissue susceptibility matched pyrolytic graphite foam. Issue 3 (14th February 2014) - Lee, Gary; Jordan, Caroline; Tiet, Pamela; Ruiz, Carlos; McCormick, Jeff; Phuong, Kevin; Hargreaves, Brian; Conolly, Steven
<x xml:space="preserve">Abstract</x> Purpose To demonstrate improved frequency selective fat suppression in MRI using a magnetic susceptibility matching foam by reducing B0 inhomogeneities induced within the body by air–tissue interfaces. Materials and Methods Flexible pyrolytic graphite (PG) composite foam was tailored to match the magnetic susceptibility of human tissue and was shaped to surround the cervical spine region. Field maps and frequency selective fat suppressed T1‐weighted FLASH images were acquired at 3 Tesla in both phantoms and six healthy necks. Results B0 field uniformity was shimmed to a target critical threshold of 1 ppm for fat suppression. The percentage of voxels in the phantom that did not achieve the critical threshold was reduced from 64% without the PG foam to only 1% with the foam. A similar decrease from 16% to 2% was observed in the in vivo region of interest. Conclusion PG foam improved B0 field uniformity by moving air–tissue field gradients outside of the neck where they cannot cause MRI artifacts. The PG foams consistently mitigated signal dropout, improved overall SNR, and enabled more robust frequency selective fat suppression. J. Magn. Reson. Imaging 2015;41:684–693. © 2014 Wiley Periodicals, Inc.